PERSEPSI PEGAWAI TENTANG PENGAMBILAN KEPUTUSAN OLEH ATASAN LANGSUNG DI KANTOR KOORDINASI PERGURUAN TINGGI SWASTA WILAYAH X (SUMATERA BARAT, RIAU, JAMBI, DAN KEPULAUAN RIAU) - Delfira . (Jurnal Bahana Manajemen Pendidikan, 2015)
The results showed that the decision by the immediate supervisor  in Kantor Kopertis Wilayah X from the aspects of: 1) decision making style 2) decision making approach 3) decision making with the acceptance decision. The problem that to writer in this research  is  decision making in Kopertis Wilayah X from the aspects  decision making style, approach and acceptance. The type of this research is descriptive. The population is all of the employees in Kantor Kopertis Wilayah X with amount 70 people and this called population research. The instruments that are used to collect the data is likert’s scale model which already put to a test for the validity and realibility. Data is analyzed by using average formula (mean). Overall decision-making is done by the immediate supervisor in Kopertis Wilayah X are in the good category with an average score of 3.83.Key word : Decision making